Edukasi Beyond Use Date (BUD) kepada Masyarakat di Puskesmas Lempake Samarinda - Samsul, Erwin; Sari, Indah Dewi; Pasaribu, Handayani; Mus, Nurul Muhlisa; Hikmawan, Baso Didik; Arifuddin, M.; Rusman, Arman; Riki, Riki; Bone, Mahfuzun; Herman, Herman; Junaidin, Junaidin; Febrina, Lizma; Ibrahim, Arsyik; Rijai, Hifdzur Rashif; Ahmad, Islamudin; Almeida, Maria; Rijai, Laode; Arifian, Hanggara (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
ABSTRACT There are still some people who do not understand the difference between the expiration date (Expired Date/ED) and the drug usage limit (Beyond Use Date/BUD). BUD is the time limit for drug use after compounding or after the primary packaging is opened. This activity aims to increase public knowledge, understanding, and awareness regarding the importance of paying attention to the safe limit for drug use or Beyond Use Date (BUD), so that people can use drugs wisely, safely, and responsibly. The activity implementation method includes counseling, material presentation, distribution of leaflets or brochures, and filling out pre-tests and post-tests. The number of participants who took part in this activity was 26 people. The results of the health promotion activity at the Lempake Community Health Center, Samarinda City showed that the average knowledge of participants about Beyond Use Date before providing education was 31.92%, and increased to 88.08% after being given information. Thus, it can be concluded that this activity was successful in increasing public knowledge regarding Beyond Use Date in the Lempake Community Health Center area, Samarinda City.. Key words: Beyond Use date (BUD), Expired date (ED), Lempake Health Center Samarinda City